A tropical bay as a reference area defined by multiple lines of evidences. Issue 1 (15th October 2017) - Pedreira, R.M.A.; Barros, F.; Farias, C. de O.; Wagener, A.L.; Hatje, V.
Abstract: References areas are sites that have undergone little or no anthropogenic impact and therefore represent the natural state of an environment. The objective of this study was to test if the Camamu Bay (CB), Bahia, can be used as a reference area for tropical coastal environments. Trace and major elements, polycyclic aromatic hydrocarbons (PAH), and the structure of the benthic macrofauna were determined. To compare the studied sites and identify the possible occurrence of anomalous concentrations, trace elements were normalized by Al and linear regressions were also performed. For all trace elements (except Cu), regressions showed a significant correlation ( p  < 0.05) and few outliers (< 3% of cases), showing that the concentrations found represent natural values for this bay. In the case of Cu, the highest concentrations were found near small municipalities, which may be associated with domestic sewage. About 60% of the organic compounds occurred at levels below the limit of quantification (< 0.26 ng g − 1 ). The sum of PAHs was low for all stations, ranging from 1.17 to 313 ng g − 1 . The benthic assemblages also indicated that the CB is a healthy, well-preserved ecosystem that deserves conservation efforts. The integrated use of geochemical and biotic data supported the use of CB as a reference area. Capsule : Organic and inorganic contaminants together with macrobenthic assemblages indicated that Camamu Bay is a pristine, tropical reference area. Graphical abstract: Highlights: Organic and inorganic contaminants indicate that Camamu bay is a pristine environment. Benthic assemblages show that Camamu is a healthy and diverse tropical bay. The use of multiple lines of evidence is essential in the characterization of reference areas. Camamu Bay promotes multiple ecological services and must be preserved.